DEVELOPMENT OF THE LEARNING MATERIALS BASED ON GUIDED INQUIRY TO FACILITATE THE STUDENTS’ EXPERIMENTAL SKILL IN ELASTICITY TOPIC - INDAH LESTARI, YULI (Inovasi Pendidikan Fisika, 2017)
The research reported in this skripsi is intended to produce the feasible learning materials (syllabus, lesson plan, assessment sheet, student’s worksheet and hand out) and to describe its feasibility. These learning materials were used to apply a learning process based on Guided Inquiry to facilitate the students’ experimental skill in Elasticity topic. The feasibility of the learning materials was based on its validity, practicability and effectiveness. The learning materials were valid when it could differentiate the students according to their abilities, and it was practical when it was easy to be used by the teachers and students. These learning materials were effective when it made the students were able to do the experiment. These aspects were tested by ADDIE model. The first work of this model was to analyze the Core Competence, Base Competence, learning materials and experimental activity in SMAN 1 Krembung. The second work was to design the prototype of the learning materials. The third, this prototype was validated to produce the final version of the learning materials. The fourth, these learning materials were implemented to 32 numbers of students in the 10th grade of Science 1 SMAN 1 Krembung. Finally, the learning materials feasibility was described. The result indicated that these learning materials were able to differentiate the 32 numbers of students’ ability, so it was very valid. These learning materials were practical because 95 % of all the activities in these learning materials were easy to be used by the teachers and students, and almost all of students gave positive responses. The 32 numbers of students were able to do the experiment in Elasticity topic with score 0.3 – 0.7 (of 0 – 1 scale). This score compared with the skill before the students used these learning materials. Consequently, 21 of 32 numbers of students passed the performance assessment with score between 79.2 and 92.7, this score is above the minimum score (78.0). According to the above results, the learning materials based on Guided Inquiry were feasible to facilitate the students’ experimental skill in Elasticity topic.   Key words: learning materials, Guided Inquiry, Students experimental skill and Elasticity.